2021
DOI: 10.7189/jogh.11.04018
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen delivery systems for adults in Sub-Saharan Africa: A scoping review

Abstract: Background Respiratory diseases are the leading cause of death and disability worldwide. Oxygen is an essential medicine used to treat hypoxemia from respiratory diseases. However, the availability and utilization of oxygen delivery systems for adults in sub-Saharan Africa is not well-described. We aim to identify and describe existing data around oxygen availability and provision for adults in sub-Saharan Africa, determine knowledge or research gaps, and make recommendations for future research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Another 65% had pulse oximeters but the quantities were inadequate and 20% had none [32]. In addition, a recent review of available studies involving adults also demonstrated a dire lack of access to oxygen delivery systems across sub-Saharan Africa with most facilities ill-equipped to identify adult patients with hypoxemia [33]. WHO guidelines on the clinical use of oxygen and technical specifications for oxygen equipment are available but emphasis is on children with specifications for adults conspicuously lacking [34].…”
Section: Discussionmentioning
confidence: 99%
“…Another 65% had pulse oximeters but the quantities were inadequate and 20% had none [32]. In addition, a recent review of available studies involving adults also demonstrated a dire lack of access to oxygen delivery systems across sub-Saharan Africa with most facilities ill-equipped to identify adult patients with hypoxemia [33]. WHO guidelines on the clinical use of oxygen and technical specifications for oxygen equipment are available but emphasis is on children with specifications for adults conspicuously lacking [34].…”
Section: Discussionmentioning
confidence: 99%
“…The outlets of the valve were connected to a zeolite column (5) each. The columns in turn were connected to the check needle valves (6). Both check needle valves were connected to the storage tank (7), which in turn was connected to the needle valve (8).…”
Section: Materials and Setup Of The Lrs Oxygen Concentratormentioning
confidence: 99%
“…The spiking demand for supplemental oxygen during this health crisis critically exposed the problem of its availability . Studies have shown that many patients in low-resource settings (LRSs) do not have access to supplemental oxygen even in hospitals. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some donations such as those related to oxygen supply require a longerterm plan to ensure infrastructure and systems are in place for proper use and management. 30 Strengthening supply chain systems to improve the process of equipment donation to and at the district level and establishing longer-term plans for certain donations will be necessary for the mutual benefit of donors and recipients alike.…”
Section: Strengthen Investments In Cross-cutting Aspects Of Health Sy...mentioning
confidence: 99%